Salsu = Night of the assassin [videorecording (DVD)] - Kwak, Chŏng-dŏk, 1969-; Sin, Hyŏn-jun, 1968-; Yi, Mun-sik, 1966-; Kim, Min'-gyŏng, 1981-; Hong, Ŭn'-gi, 1997- (Well Go USA Entertainment, 2023)
Joseon, the last and longest dynasty in Korea, spanned over 500 years and contained some of the greatest unrivaled assassins. One such assassin discovers he has a heart condition and must put his violent career aside while he searches for a cure. With a bounty on his head and an area gang barging into his village hide-out, he must again assume his sword and fight to survive.